2018
DOI: 10.1007/s10942-018-0292-8
|View full text |Cite
|
Sign up to set email alerts
|

A Historical and Theoretical Review of Cognitive Behavioral Therapies: From Structural Self-Knowledge to Functional Processes

Abstract: This paper critically examines the historical conceptualization of cognitive behavioral psychotherapy approaches (CBT) as a direct clinical counterpart of the cognitive revolution. The main “second wave” cognitive psychotherapies, either standard cognitive therapy (CT) or constructivist, in spite of their differences, share a common conceptualization of psychopathological factors as superordinate structural cognitive content belonging to the self: self-beliefs, self-schemata, personality organizations and so o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 109 publications
1
30
0
2
Order By: Relevance
“…The more interesting fact is, CBT is so well explained and standardized, that there is almost no difference if we offer personal or group‐based CBT interventions (Cuijpers, van Straten, & Warmerdam, 2008; Epstein et al, 2018; Kodal et al, 2018; Wolgensinger, 2015). The main premise of CBT treatment is that the way how we think about certain situations and how we behave in them will affect how we feel about them (Ruggiero, Spada, Caselli, & Sassaroli, 2018). Based on that, the main goal of CBT would be to offer cognitive and behavioural strategies and techniques to change someone's thoughts, beliefs, expectations, attitudes, and behaviour towards ourselves, others, and/or living conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The more interesting fact is, CBT is so well explained and standardized, that there is almost no difference if we offer personal or group‐based CBT interventions (Cuijpers, van Straten, & Warmerdam, 2008; Epstein et al, 2018; Kodal et al, 2018; Wolgensinger, 2015). The main premise of CBT treatment is that the way how we think about certain situations and how we behave in them will affect how we feel about them (Ruggiero, Spada, Caselli, & Sassaroli, 2018). Based on that, the main goal of CBT would be to offer cognitive and behavioural strategies and techniques to change someone's thoughts, beliefs, expectations, attitudes, and behaviour towards ourselves, others, and/or living conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The process model of emotion regulation is relevant to psychopathology (Sheppes et al, 2015), and to psychotherapies implementing cognitive change (e.g., Hofmann et al, 2012). Cognitive change, as presented in Gross' (2014) process model, is predicated on the axiomatic principle imbedded within second-wave cognitive behavioural psychotherapies (CBTs), that cognitions mediate between the environment and our emotional responses (Mahoney, 1974;Ruggiero et al, 2018). In other words, in the face of an adverse situation, our thoughts about the event largely determines our emotional reactions.…”
mentioning
confidence: 99%
“…21,32,33 A division of the components of CBT has suggested that BA components of CBT work as well as cognitive mechanisms, such as cognitive restructuring of dysfunctional CBs; 34 a finding that has been replicated. 23 In the past 60 years, several approaches have been influenced by behavioral and cognitive therapies, such as conventional CBT, a label that encompasses several protocols emphasizing cognitive mediation, 14,[35][36][37] such as schema therapy, compassion-focused therapy, behavioral activation, acceptance and commitment therapy, dialectic behavioral therapy, etc., and, in the last 10 years, trial based-cognitive therapy (TBCT). These psychotherapy models are differentiated by both the theories and the ways of approaching behaviors and thoughts.…”
Section: Introductionmentioning
confidence: 99%
“…These psychotherapy models are differentiated by both the theories and the ways of approaching behaviors and thoughts. 35,38 TBCT was developed in Brazil, based on Aaron Beck's CBT model, but with its own case conceptualization and techniques. Among TBCT distinctive features, the following can be underscored: it provides an integrative conceptualization of psychopathology; presents a set of step-by-step cognitive and behavioral techniques; introduces a new systematic approach to change dysfunctional core beliefs; it was designed as an overall easy-to-remember case-formulation model both for the therapist and the patient; integrating cognitive, emotional, and experiential work simultaneously.…”
Section: Introductionmentioning
confidence: 99%